Pengaruh Persepsi Return, Risiko, Pengetahuan dan Religiusitas Terhadap Minat Berinvestasi di Pasar Modal Syariah - Prasetio, Rudi; Iswanji, Chaidir; Khotijah, Siti Afidatul (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2023)
In its development, the Islamic capital market in Indonesia has experienced various obstacles, especially during the Covid-19 pandemic that hit the world in recent years, which is thought to be the main cause due to the low level of knowledge of the Islamic capital market and public interest in the Islamic capital market. Therefore, the purpose of this study is to find out what factors are expected to influence the dependent variable, namely the interest in investing in the Islamic capital market, which includes perceived return, perceived risk, investment knowledge, and religiosity. This research is a type of quantitative research using primary data from research objects which are KSPM Ahmad Dahlan University (UAD) and Yogyakarta Muhammadiyah University (UMY) with a total sample of 60 respondents using a sampling technique that is simple random sampling. Tests carried out include descriptive statistical tests, validity and reliability tests, classical assumption tests, multiple linear regression tests, hypothesis testing (F test and t test), and test the coefficient of determination. Based on the results of this study, the results show that: Partially only the variable perceived return has a positive and significant effect on the dependent variable so that H1 is accepted, and for H2, H3, and H4 it is partially obtained that these variables have no effect on the dependen variable, therefore H2, H3, and H4 rejected..